Cavity Shaving plus Lumpectomy versus Lumpectomy Alone for Patients with Breast Cancer Undergoing Breast-Conserving Surgery: A Systematic Review and Meta-Analysis. - Ke Wang; Yu Ren; Jianjun He (PLoS ONE)
The margin status is a well-established prognostic predictor for patients undergoing breast-conserving surgery (BCS). Recent data suggested that cavity shaving in addition to lumpectomy might be a promising approach for improving the clinical outcomes. We aimed to compare the efficacy and safety between cavity shaving plus lumpectomy and lumpectomy alone with a systematic review and meta-analysis. We searched the PubMed, Embase, and Cochrane CENTRAL databases for studies comparing cavity shaving with lumpectomy before June 10, 2016. Both comparative studies and self-control studies were included. A random-effects model was used to estimate the odds ratios (ORs) for positive margin rate, reoperation rate, recurrence rate, and weighted mean difference (WMD) for excised tissue volume. Twenty-six studies were included in the meta-analysis. The cavity shaving group had a significantly lower positive margin rate than the BCS-alone group (16.4% vs. 31.9%; OR = 0.41, 95% CI 0.32-0.53, P < 0.05). Cavity shaving was associated with a significantly decreased rate of reoperation (OR = 0.42, 95% CI 0.30-0.59, P < 0.05). The overall locoregional rate was low for cavity shaving and BCS-alone (3% vs. 4%). Cavity shaving had no significant effect on the risk of locoregional recurrence (OR = 0.86, 95% CI 0.32-2.35; P = 0.78). The excised tissue volume did not differ substantially between cavity shaving and BCS alone (WMD = -23.88, 95% CI -55.20 to 7.44, P = 0.14). For patients undergoing BCS, additional cavity shaving was an effective method to decrease the positive margin rate and avoid reoperation. The addition of cavity shaving did not appear to have excessive excised tissue volume compared with partial mastectomy alone.